(untitled) - Mizutani, Osamu (Tokyo, 1977)
The book introduces around 450 kanji-words, which is about what Japanese For Everyone covers. The Kanji-characters are usually introduced as words, so you don't learn every possible on/kun pronunciation for each character.
Keywords: Japanese language; Textbooks for foreign speakers